The Development and Validation of the Health Behavior Motivation Scale - Poraj-Weder, Magdalena; Pasternak, Aneta; Szulawski, Michał (Frontiers in Psychology, 2021)
The article presents the construction and validation process of the Health Behavior Motivation Scale (HBMS), which measures the motivation towards pro-health behaviors in population of healthy adults. The tool is conceptually based on Self-Determination Theory (SDT; Deci & Ryan, 2000, and more precisely on one of its subtheories – Organismic Integration Theory (OIT; Ryan & Deci, 2017). In the first stage of the construction, the linguistic validation with competent judges procedure allowed to eliminate the items which were not correctly formulated. Next, the psychometric properties of the HBMS were assessed in three studies. In Study 1 (N = 323, Mage = 31), the factorial structure of the HBMS was assessed with CFA. Since the preliminary structure was rejected, in order to identify the dimensionality of the items, EFA and Horn’s Parallel Analysis were performed. The results showed that the HBMS scale has 5–dimensional structure (intrinsic regulation, integrated and identified regulation, introjected regulation, external regulation and amotivation). In Study 2 (N = 342, Mage = 33), the structure of the HBMS has been confirmed by conducting CFA analysis. Analyses preformed in this study provided good evidence for convergent and discriminant validity as well as the internal reliability of the HBMS subscales. Finally, in the LPA analysis two classes with distinct regulatory profiles have been extracted, which showed differences in the extend of health-related behaviors. In Study 3 (N = 60, Mage = 30) the test–retest reliability of the HBMS was confirmed. The scale can be therefore successfully used in future basic and applied studies as it possesses robust psychometric properties.